Wound-Healing Potential of the Root Extract of Albizzia lebbeck - Joshi, Apurva; Sengar, Nidhi; Prasad, Satyendra K.; Goel, Raj Kumar; Singh, Akanksha; Hemalatha, Siva (Planta Medica, 2013)
The present investigation is an attempt to scientifically validate the traditional use of the roots of the plant Albizzia lebbeck in Ayurvedic system of medicine for curing wounds. The study included phytochemical standardization of the ethanol root extract of A. lebbeck, which was further subjected to oral acute toxicity study. Wound-healing activity of the ethanol root extract was evaluated using incision and excision wound models. Biochemical parameters such as hydroxyproline, hexuronic acid, hexosamine, and antioxidant enzymes like superoxide dismutase, reduced glutathione and free radical parameters including lipid peroxidation and nitric oxide were evaluated on the 10th post-wounding day following dead space method. For confirmation of activity, histopathology of the wounds and granulation tissues from excision and dead space wound model were performed. The study also included assessment of antibacterial activity of ethanol root extract against strains implicated in wound infection. The ethanol root extract was found to be highly rich in flavonoids, saponins, phenols, and tannins, while the amount of rutin was found to be 4.66 % w/w. It significantly increased the wound breaking strength showing a ceiling effect at 500 mg/kg p. o. The ethanol root extract at 500 mg/kg p. o. depicted an optimum wound contraction on the 18th day, while complete wound contraction was observed at the 22nd post wound day. It also demonstrated a significant increase in dry tissue weight, total protein, hydroxyproline, hexosamine, hexuronic acid, superoxide dismutase, and reduced glutathione levels, whereas a decrease in the levels of lipid peroxidation and nitric oxide was also observed with a potential antibacterial activity. Histopathological studies revealed a normal epithelization and fibrosis which was evidenced through an increase in collagen density. Thus, the study scientifically validated the wound-healing activity of the ethanol root extract along with a potential antibacterial property which may be attributed to the enhanced collagen synthesis and a potential antioxidant activity.
Keywords: Albizzia lebbeck; Fabaceae; excision wounds; ethanol extract; incision wounds; skin wound healing